3D conductive network wrapped CeO2-x Yolk@Shell hybrid microspheres for selective-frequency microwave absorption. (June 2020) - Li, Qingqing; Zhao, Yunhao; Wang, Lei; Zhang, Jie; Li, Xiao; Che, Renchao
Abstract: Carbon nanotubes (CNTs) based materials have been popular as microwave absorbers owing to their tunable electrical conductivity. Here, a hierarchical CeO2-x yolk@shell microsphere encapsulated by the CeO2-x /CNTs hybrid three-dimensional (3D) conductive network (denoted as CMC) was successfully fabricated by a simple solvothermal method through a cooperative-assembly strategy owing to a synergistic effect of reactants. The well-designed hierarchical structure is beneficial to optimize the electrical conductivity for the dielectric-dominated microwave absorber, resulting in the enhanced electromagnetic impedance matching and energy dissipation ability. Importantly, the primary units made up of conductive CNTs and insulated CeO2-x nanoparticles simultaneously provide large room for resistivity adjustment and abundant of localized polarized sites. Moreover, the hierarchical dielectric structure is similar to a microwave trapping cage in micro-meter size can effectively dissipates microwave energy. Thus, the strong microwave absorption (−52.4 dB at 6.1 GHz) and selective-frequency response (shift from 5.2 GHz to 18 GHz) can be achieved through regulating the composite conductivity only by tailoring the input amount of oxidized CNTs. Considering the promising performance of the CMC yolk@shell@shell microspheres, this work is expected to enlighten the design and synthesis of the carbon-based materials in other related fields. Graphical abstract: Image 1